(3GdQbGHI GdeUQajI hGdJfXje GdEMJQGRj GdLRGFQj (B/s - (3HhHcQ, eUWais ((3GdLRGFQ(B: s (3OGQ gheI(B, s, 2019)
(3GdGTQGa hGdQbGHI GdeUQajI aj GdfXGe GdeUQaj GdLRGFQj, JYQja hJTcjd hGSJbdGdjI GdHfc GdLRGFQj ef NdGd GdQbGHI GdGMJQGRjI hcPdc eaghe GdHfhc GdJLGQjI hGdeDSSGJ GdeGdjI HGdGVGaI Gdi GdYedjGJ GdeUQajI hab bGfhf GdfbO hGdbQV, hcjajI GdJfXje GdGMJQGRj aj gPG GdfXGe eY JHfj eYGjjQ GMJQGRjI eSJeOI ef ebQQGJ HGRd(B3 (3hGOGQI eNGWQ GdGFJeGf Vef GdfXe GdGMJQGRjI GdLOjOI aj GdLRGFQh JbSjegG ef GdNWQ GdYedjGJj hNWQ GdShb hGdUQa hGdSjhdI(B.s
(3eQGLY U(B.69s
Keywords: (3GdHfhc(B- (3GdLRGFQs; (3GdJfXjes; (3GdQbGHIs